Sejarah Perkembangan Manajemen Mutu Pendidikan Islam - Muhammad Andreansyah Hidayatulloh (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
Quality management in Islamic education is a response to the need for improved institutional quality, adapting to societal changes and the evolving times. This research investigates the historical development of quality management concepts in Islamic education, from classical periods to the modern era, using a historical-qualitative library research approach that draws from primary and secondary sources. Findings reveal that since ancient times, quality has been ingrained in Islamic values through the principles of ihsan, itqan, and amanah, evident in madrasah and pesantren systems. In contemporary times, quality management, including approaches like Total Quality Management (TQM), has been integrated with Islamic spiritual values, leading some Islamic educational institutions to successfully implement national and international quality standards to boost competitiveness. This demonstrates that effective quality management hinges not just on administrative systems but also on deeply internalizing Islamic values across all educational facets.